Research of the problem of ensuring the country's food security in the context of the volatility of the external environment: bibliometric analysis (Journal of Economic Research & Business Administration, 2023)
At present, especially in conditions of instability and uncertainty, the issues of food security, food independence of the country are becoming more and more relevant, and the solution of this problem is one of the main conditions for the sustainable development of any state or individual regions. Thus, the issue of ensuring food safety is one of the most pressing issues, both at the national and global levels.The article deals with the issue of ensuring the country's food security in the context of the Covid-2019 pandemic and its consequences, the tension occurring around the world, the variability and complexity of the general external environment. The problem under study is widely considered in the works of foreign and domestic scientists. The main methods and concepts used in scientific works are determined, and the comparative characteristics of the studies are analyzed. The article discusses the directions of development of research in the field of food safety. This topic is widely reflected in the research of scientists. The study is based on the use of methods and tools of bibliometric analysis (R-package Bibliometrix): 681 scientific papers were selected from the Scopus database; the analysis makes it possible to analyze the direction and level of development of research on the problem of food security.Keywords: food security, environment variability, literature review, bibliometric analysis